IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI BUDAYA SEKOLAH DI SMK NEGERI 7 KOTA BENGKULU 2022/023: Pendidikan Karakter Melalui Budaya Sekolah - Muhamad Martin Wibowo Kusumo; Amnnah Qurniati (Jurnal Pancasila dan Kewarganegaraan (JUPANK), 2023)
Abstract This research aims to find out: (1) How is the implementation of character education through school culture at SMK Negeri 7 Bengkulu City, (2) How are the obstacles faced at SMK Negeri 7 Bengkulu City in implementing character education through school culture at SMK Negeri 7 Bengkulu City, (3) How are efforts made in implementing character education through school culture at SMK Negeri 7 Bengkulu City. The research method used is descriptive qualitative method. The natural sampling technique of this research uses the Snowball Sampling technique. The data collection process used in this research is observation, interview, and documentation. Based on the results of the study, it was found that: (1) The implementation of character education through school culture at SMK Negeri 7 Bengkulu City has been implemented through activities in the school. Character values that have been implemented at SMK Negeri 7 Kota include religious values, love for the country, discipline, responsibility, care for the environment. (2) Obstacles to the implementation of character education through school culture at SMK Negeri 7 Bengkulu City include teachers, students, activities or habituation at school, infrastructure, and the school environment. Efforts made in the implementation of character education through school culture at SMK Negeri 7 Bengkulu City include teachers who have maximized the implementation of School Culture, students who are enthusiastic and enthusiastic, the role of parents in helping the school and infrastructure. Keyword: Implementation, Character Education, School Culture